An advanced conduction based heat pipe model accounting for vapor pressure drop. (August 2021) - Zimmermann, Sascha; Dreiling, Robert; Nguyen-Xuan, Thinh; Pfitzner, Michael
Highlights: A novel conduction-based method for calculating heat pipe performance is presented. An analytic expression for calculating the axial pressure gradient is developed. The ratio of Hagen to Reynolds number is used to model vapor thermal conductivity. The pressure gradient inside a heat pipes vapor core is reliably predicted. At low temperatures, pressure drop significantly affects heat pipe thermal resistance. Abstract: Heat pipes are passive heat transfer devices which play an increasingly important role in state-of-the-art cooling solutions for various technologies like consumer electronics or electric machines. During design phase, reliable simulation results are the key for optimal performance and efficiency. In system level simulations, heat conduction models, characterized by low computational effort, are widely used to predict heat pipe thermal resistance. In order to accurately calculate overall thermal characteristics, a precise prediction of the vapor core's temperature drop is crucial. In this study, a novel conduction-based method for calculating heat pipe performance is presented. Taking velocity components perpendicular to the main vapor flow into account, an analytic expression for calculating the axial pressure gradient is developed and validated through detailed CFD simulations. Assuming saturation conditions, results are used to determine the vapor core's local effective thermal conductivity. Parameters needed for calculation are provided for both circular and flat heat pipes under various operating conditions. The final model accounts for phase change thermal resistance and temperature dependent fluid properties. The presented method yields significantly different results compared to state-of-the-art approaches in which thermal vapor resistance is either assumed to be zero or calculated assuming (Hagen-)Poiseuille flow. Simulation results suggest a strong dependence of vapor thermal resistance on evaporation and condensation mass fluxes, thermophysical fluid properties and local vapor temperature.